Novel thermal and non-thermal technologies for fluid foods - Cullen, P. J.; Tiwari, Brijesh K.; Valdramidis, Vasilis P. (London : Elsevier/Academic Press, 2012)
Food processing is the step of the food chain that principally affects a food's physical or biochemical properties, along with determining the safety and shelf life of the product. This book provides a comprehensive overview of innovations in non-thermal technologies specifically for fluid foods, recognized for their high bioavailability of macronutrients and micronutrients. Considerable resources and expertise has been devoted to the processing of safe and wholesome foods. Non-thermal technologies have been developed as an alternative to thermal processing, while still meeting required safety or shelf-life demands and minimising the effects on its nutritional and quality attributes.
1. Status and trends of novel thermal and non-thermal technologies for fluid foods -- 2. Fluid dynamics in novel thermal and non-thermal processes -- 3. Fluid rheology in novel thermal and non-thermal processes -- 4. Pulsed electric field processing of fluid foods -- 5. High pressure processing of fluid foods -- 6. Ultrasound processing of fluid foods -- 7. Irradiation of fluid foods -- 8. Ultraviolet and pulsed light processing of fluid foods -- 9. Ozone processing of fluid foods -- 10. Dense phase carbon dioxide processing of fluid foods -- 11. Ohmic heating of fluid foods -- 12. Microwave heating of fluid foods -- 13. Infrared heating of fluid foods -- 14. Modeling the kinetics of microbial and quality attributes of fluid food during novel thermal and non-thermal processes -- 15. Regulatory and legislative issues for thermal and non-thermal technologies : an EU perspective
Includes bibliographical references and index
Keywords: Fluids; Food industry and trade; Food -- Preservation